Analysis of the Causes of Road Damage - Edison Hatoguan Manurung; Kasimir Sawito; Aryo Satoto; Nurbaya Tuanany (Litbang Pemas - Universitas Islam Lamongan, 2022)
Road infrastructure as the lifeblood of the transportation system which plays an important role in supporting various aspects of life, thus must always be in good condition so that it can continue to contribute to improving services optimally through repair and maintenance. The handling of damage to flexible pavement construction in the form of maintenance, rehabilitation and road improvement has not been carried out optimally. This is possible when carrying out maintenance only on physical damage by not conducting ongoing evaluations of other possible causal factors that must be anticipated so that the road pavement does not experience the same damage. The description of this research is on various road damage and various factors causing damage in various regions in Indonesia, then the relationship between road damage. Using relevant research/previous literature review methods. According to the results of the analysis, road damage is known to dominate crack damage and surface defects. Then, the main factor causing road damage is that drainage maintenance is not carried out regularly and properly so that a lot of garbage clogs up or around the platform grows a lot of plants. Thus, road bodies and other road pavement complementary buildings that are well maintained show a significant type, severity and amount of pavement damage, which causes the repair process. must be done immediately